The effects of COVID-19 on the vestibular system - Zaubitzer, Lena; Ludwig, Sonja; Berkemann, Michelle; Walter, Beatrice; Jungbauer, Frederic; Held, Valentin; Hegemann, Stefan C. A.; Rotter, Nicole; Schell, Angela (Frontiers in Neurology, 2023)
Introduction The symptoms and severity of SARS-CoV-2 infection vary greatly across the spectrum, from asymptomatic infection to severe pneumonia with acute respiratory distress syndrome and even death. Dizziness is a frequently reported symptom of SARS-CoV-2 viral infection. However, the extent to which this symptom results from the effect of SARS-CoV-2 on the vestibular system remains unclear. Materials and methods In the present single-center, prospective cohort study, patients with a previous SARS-CoV-2 infection underwent a vestibular assessment consisting of the Dizziness Handicap Inventory to assess dizziness during and after infection, a clinical examination, the video head impulse test, and the subjective visual vertical test. When the subjective visual vertical test result was abnormal, vestibular-evoked myogenic potentials were performed. Vestibular testing results were compared to pre-existing normative data of healthy controls. In addition, we performed a retrospective data analysis of patients admitted to hospital presenting with acute symptoms of dizziness who were also diagnosed with acute SARS-CoV-2 infection. Results A total of 50 participants have been enrolled. During and after the SARS-CoV-2 infection, women were significantly more likely than men to suffer from dizziness. A significantly reduced semicircular canal or otolith function was not observed in either women or men. Acute SARS-CoV-2 infection was diagnosed in nine patients who presented to the emergency room with acute vestibular syndrome. Six of the patients exhibited acute unilateral peripheral vestibulopathy upon diagnosis. A different patient was diagnosed with vestibular migraine, and two individuals had a posterior inferior cerebellar artery infarct revealed by magnetic resonance imaging. Discussion/conclusion Overall, a persisting structural affection of the vestibular system by SARS-CoV-2 seems to be unlikely and could not be confirmed by vHIT, SVV, and VEMPS in our study. It seems possible but unlikely that SARS-CoV-2 induces acute vestibulopathy. Nevertheless, dizziness is a common symptom in patients with COVID-19, which should be taken and worked through seriously.